Condylar asymmetry in different occlusion types. Issue 1 (January 2015) - Kasimoglu, Yelda; Tuna, Elif Bahar; Rahimi, Boragh; Marsan, Gulnaz; Gencay, Koray
Abstract : Aims: The purpose of this study was to investigate the relationship between vertical asymmetries of the mandibular condyle with different occlusion types, including Angle Cl I, Cl II, Cl III malocclusions and unilateral posterior crossbite (UPC) in adolescent patients. Methodology: A total number of 120 patients (60 girls, 60 boys with a mean age of 13·64±1·58 years) with no signs and symptoms of temporomandibular disorders were included in the study [ n  = 30 for each group; Group I: normal occlusion, Group II: Angle Class II malocclusion, Group III: Angle Class III malocclusion and Group IV: UPC]. The asymmetry index for each patient was measured using panoramic radiographs. The results were analyzed using Kruskal–Wallis and Mann–Whitney U test at the 95% confidence level. Results: The results of the analyses showed no statistically significant differences between the gender and the age of the patients for condylar height asymmetry ( P >0·05). No statistically significant difference was found between the occlusion types, according to condylar asymmetry level. The patients with UPC showed a significantly different level of condylar height asymmetry compared to the Class I, II and III occlusion types ( P <0·05; P <0·01). Conclusions: Patients with UPC have asymmetric condylar heights. These patients might be at risk for developing skeletal mandibular asymmetries in the future. Early correction of posterior crossbite can help practitioners prevent skeletal asymmetries.